2018
DOI: 10.1681/asn.2017121338
|View full text |Cite
|
Sign up to set email alerts
|

The Human FSGS-Causing ANLN R431C Mutation Induces Dysregulated PI3K/AKT/mTOR/Rac1 Signaling in Podocytes

Abstract: The mutation causes multiple derangements in podocyte function through hyperactivation of PI3K/AKT/mTOR/p70S6K/Rac1 signaling. Our findings suggest that the benefits of calcineurin inhibition in FSGS may be due, in part, to the suppression of ANLN and mTOR. Moreover, these studies illustrate that rational therapeutic targets for familial FSGS can be identified through biochemical characterization of dysregulated podocyte phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 43 publications
(56 reference statements)
2
46
0
Order By: Relevance
“…Previous studies have suggested that PI3K and Rac have different downstream‐upstream linkages or that PI3K and Rac may be independent . In this study, we found that PPF and the subsequent platelet shedding triggered by MT primarily depended on the activation of PI3K‐Akt/Rac pathway.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Previous studies have suggested that PI3K and Rac have different downstream‐upstream linkages or that PI3K and Rac may be independent . In this study, we found that PPF and the subsequent platelet shedding triggered by MT primarily depended on the activation of PI3K‐Akt/Rac pathway.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies have suggested that PI3K and Rac have different downstream-upstream linkages or that PI3K and Rac may be independent. [42][43][44] In this study, we found that PPF and the subsequent platelet shedding triggered by MT primarily depended on the activation of PI3K-Akt/Rac pathway. Furthermore, we also found that both Akt and Rac act downstream of PI3K, Rac also served as a direct downstream target of PI3K.…”
Section: Discussionmentioning
confidence: 56%
“…8 Previous studies have found that ANLN can regulate actin cytoskeletal dynamics in podocytes. 9 Previous studies have also confirmed that ANLN expression is associated with prognosis in patients with breast, 10 bladder, 11 and colorectal cancers. 12 Pandi et al 13 confirmed that ANLN is a Wnt/β-catenin responsive gene in gastric cancer and can regulate the proliferation of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 83%
“…Anillin has attracted increasing attention as a potential disease-related gene (ORPH:93213, OMIM:616027). Evidence point at anillin expression levels being associated with cell proliferation and migration disorders in cancer and kidney diseases [146][147][148][149] . Additional roles for this actin binding protein have been reported in nerve cell development 150,151 and dysregulation of Anillin has been implicated in central nervous system myelin disorders 152,153 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that anillin expression is positively associated with the expression of β-catenin (ctnnb1) 154 consistent with ctnnb1 also being an Atoh7-downregulated gene in our gene cohort. Furthermore, Anillin appears to be an essential regulator of epithelial cell-cell adherens junctions via regulation of the E-Cadherin/β-catenin complex 148,155,156 . In agreement with this idea, we here make the preliminary observation that anillin knock down results in accumulation and displacement of β-catenin signal in the apical and apical-lateral membrane of RPCs (Supp.…”
Section: Discussionmentioning
confidence: 99%